Realization of the autonomous region through noncooperation and state cooperation - Zikri Muhammad, Nellis Mardhiah, Rahma Hidayati, Afrizal Tjoetra, Mursyidin, (Opción, 2020)
The supporters of the pluralist approach argue that countries and non-states play an important role in international relations. Using qualitative methods that emphasize the analysis of past studies, documents, and secondary materials, this paper examines more deeply in terms of the role of the state and non-state in the case of Aceh and Mindanao. The findings show that cooperation between actors and non-state plays an important role in the birth of the autonomous region. In conclusion, the cooperation of political stability in the conflicting territories can be restored in cooperation with the actors of the state and non-state.